Пиролиз углеводородного сырья - Мухина Т. Н. Тамара Николаевна; Барабанов Н. Л. Николай Леонидович; Бабаш С. Е. Софрина Ефимовна; Аврех Г. Л. Геннадий Липанович (Москва, Химия, 1987)
Авт. указаны на обороте тит. листа